Phenotyping of Sleep‐Disordered Breathing in Patients With Chronic Heart Failure With Reduced Ejection Fraction—the SchlaHF Registry. Issue 12 (29th November 2017) - Arzt, Michael; Oldenburg, Olaf; Graml, Andrea; Erdmann, Erland; Teschler, Helmut; Wegscheider, Karl; Suling, Anna; Woehrle, Holger; ,
Abstract : Background: Different sleep‐disordered breathing (SDB) phenotypes, including coexisting obstructive and central sleep apnea (OSA‐CSA), have not yet been characterized in a large sample of patients with heart failure and reduced ejection fraction (HFrEF) receiving guideline‐based therapies. Therefore, the aim of the present study was to determine the proportion of OSA, CSA, and OSA‐CSA, as well as periodic breathing, in HFrEF patients with SDB. Methods and Results: The German SchlaHF registry enrolled patients with HFrEF receiving guideline‐based therapies, who underwent portable SDB monitoring. Polysomnography (n=2365) was performed in patients with suspected SDB. Type of SDB (OSA, CSA, or OSA‐CSA), the occurrence of periodic breathing (proportion of Cheyne‐Stokes respiration ≥20%), and blood gases were determined in 1557 HFrEF patients with confirmed SDB. OSA, OSA‐CSA, and CSA were found in 29%, 40%, and 31% of patients, respectively; 41% showed periodic breathing. Characteristics differed significantly among SDB groups and in those with versus without periodic breathing. There was a relationship between greater proportions of CSA and the presence of periodic breathing. Risk factors for having CSA rather than OSA were male sex, older age, presence of atrial fibrillation, lower ejection fraction, and lower awake carbon dioxide pressure (Pco 2 ). Periodic breathing was more likely in men, patients with atrial fibrillation, older patients, and as left ventricular ejection fraction and awakePco 2 decreased, and less likely as body mass index increased and minimum oxygen saturation decreased. Conclusions: SchlaHF data show that there is wide interindividual variability in the SDB phenotype of HFrEF patients, suggesting that individualized management is appropriate. Clinical Trial Registration: URL:https://www.clinicaltrials.gov/ . Unique identifier: NCT01500759.